A Dictionary of Slovak Neologisms (A Project Description). (23rd February 2021) - Ološtiak, Martin; Rešovská, Soňa
Abstract: The paper presents the project focusing on neologisms in the Slovak language, the main outcome of which is A Dictionary of Slovak Neologisms (DSN), a specialized restricted dictionary of a certain lemma type. The first part introduces general remarks including relations of extralinguistic reality with the lexicon of a natural language. In the second section, elementary terminology (language change, lexical change, innovation, neologism, neology, newness) is outlined. In the third section, the project of the DSN is introduced. The dictionary aims to provide linguistic (lexicographic) information on approximately 13, 000-15, 000 new words, meanings and expressions. When compiling the dictionary, the synchronic-diachronic perspective is taken into account. This indicates that lexical units that came into existence in the Slovak language after 1989 are included. The publication of the dictionary is planned for 2023, both in printed and electronic form, with the latter intended to be available online.